Screening of blood and mucus parameters towards breeding for resistance to salmon louse (lepeophtheirus salmonis) in atlantic salmon - Amit, Das (2013)
Over the last three decades salmon farmers have experienced serious economic hardships due to losses caused by sea lice (Lepeophtheirus salmonis) infestations. In the absence of an effective vaccine, inefficiency of biological control methods and growing concerns over the usage of chemical treatments, there is a quest for alternative strategies to combat this problem. This includes selective breeding approach to increase the innate resistance in fish to the parasite. There is hope that easily measured biomarkers that are correlated to sea lice resistance, exist and can be used to ease recording, reduce cost and increase genetic gain for sea lice resistance. Indications of additive genetic difference in lice resistance in Atlantic salmon (Salmo salar) have led us to hypothesize that biomarkers of resistance are present in the plasma and/or mucus of fish. High throughput Fourier Transform Infrared (FT-IR) profiling of plasma and mucus together with screening of the selected blood parameters (with the help of i-STAT blood gas analyzer) were coupled with multivariate statistical analysis to investigate the differences between two groups (susceptible (S) and Resistant (R)) of Atlantic salmon that shown different in their susceptibility to sea lice. The assignment was based on the sea lice challenge test results of their full-sibs. 65 rainbow trout (Oncorhychus mykiss) were also included in this trial in order to study the species-specific differences for this trait. Fish was challenged twice between late November and early December 2008 and lice were counted for the first time in December 2008 (chalimus sessile stage), followed by second count in January 2009 (pre-adult motile stage) and finally in February 2009 (adult motile stage). A large variation in lice counts both between individual Atlantic salmon and individual rainbow trout was observed. With respect to lice count, S and R groups of Atlantic salmon were different in both sessile and motile stages of lice, indicating genetic background for this trait. ...